An updated view of plasmid conjugation and mobilisation in Staphylococcus - Ramsay, Joshua; Kwong, S.; Murphy, Riley; Yui Eto, Karina; Price, Karina; Nguyen, Quang; O'Brien, Frances; Grubb, Warren; Coombs, Geoffrey; Firth, N. (2016)
The horizontal gene transfer facilitated by mobile genetic elements impacts almost all areas of bacterial evolution, including the accretion and dissemination of antimicrobial-resistance genes in the human and animal pathogen Staphylococcus aureus. Genome surveys of staphylococcal plasmids have revealed an unexpected paucity of conjugation and mobilization loci, perhaps suggesting that conjugation plays only a minor role in the evolution of this genus. In this letter we present the DNA sequences of historically documented staphylococcal conjugative plasmids and highlight that at least 3 distinct and widely distributed families of conjugative plasmids currently contribute to the dissemination of antimicrobial resistance in Staphylococcus. We also review the recently documented "relaxase-in trans" mechanism of conjugative mobilization facilitated by conjugative plasmids pWBG749 and pSK41, and discuss how this may facilitate the horizontal transmission of around 90% of plasmids that were previously considered non-mobilizable. Finally, we enumerate unique sequenced S. aureus plasmids with a potential mechanism of mobilization and predict that at least 80% of all non-conjugative S. aureus plasmids are mobilizable by at least one mechanism. We suggest that a greater research focus on the molecular biology of conjugation is essential if we are to recognize gene-transfer mechanisms from our increasingly in silico analyses.